A review of the fernane-type triterpenoids as anti-fungal drugs - Liu, Chun-Yue; Zhang, Lu; Liu, Si-Xuan; Lu, Yong-Fu; Li, Chang; Pei, Yue-Hu (Frontiers in Pharmacology, 2024)
Human fungal pathogens could cause a broad plethora of infections in both the immunocompetent and immunocompromised host. Fungal infections have become important causes of morbidity and mortality in recent years, the current arsenal of anti-fungal therapies was restricted.Ibrexafungerp was a novel, highly bioavailable glucan synthase inhibitor formulated for both intravenous and oral administration being developed by Scynexis; it was also the first novel antifungal drug class approved in more than 20 years. Ibrexafungerp was one semi-synthetic derivative of enfumafungin, a natural product isolated from fungi. This review reported the discovery of enfumafungin and ibrexafungerp, their anti-fungal mechanism, summed up 63 fernane-type triterpenoids from natural products, including 49 from plants, 9 from fungi and 5 from lichen. In addition, the review summarized the progress of enzymes responsible for the biosynthesis of type II fernane triterpenoid (enfumafungin skeleton) and type I fernane triterpenoid (polytolypin skeleton).The good example kept our confidence up for searching for new leading compounds and discovering drugs from fungi.